AVALIAÇÃO DOS EFEITOS DO EXTRATO ETANÓLICO DE ALTERNANTHERA LITTORALIS, SALVIA LACHNOSTACHYS BENTH E SERJANIA ERECTA NO DESEMPENHO REPRODUTIVO, DESENVOLVIMENTO EMBRIOFETAL E INTEGRIDADE DO DNA EM CAMUNDONGOS SWISS - Hudman Cunha Ortiz (2023)
Since the beginning of human history, there have been records that traditional medicine has used medicinal plants to treat diseases, including during pregnancy and childbirth. These practices are increasingly common and can be incorporated into modern medical practices. Alternanthera littoralis is used in Brazilian folk medicine for the treatment of inflammatory and infectious diseases. Salvia lachnostachys Benth is native to Brazil and is popularly used as anti-inflammatory, anti-arthritic and anti-hyperalgesic. Serjania erecta leaf tea is popularly used in Brazil against ulcers and its roots against hypertension, in addition to being used against stomach disorders. There are no records in the literature of the effects of prolonged use of these plants on the pregnant woman and the fetus. Therefore, the present study aimed to evaluate the effects of Ethanol Extracts of Alternanthera littoralis (EEAl), Salvia lachnostachys Benth (EESl) and Serjania erecta (EESe) on reproductive performance, embryofetal development and DNA integrity of female mice swiss pregnant. In the first and second studies, Alternanthera littoralis and Salvia lachnostachys Benth, respectively, pregnant females were randomly assigned to 3 experimental groups (n = 10): Control group treated with vehicle and groups EEAl/EESl 100 and EEAl/EESl 1000 treated with doses of 100 and 1000 mg/kg, respectively. In the third study, with Serjania erecta, pregnant females were randomly distributed into 4 experimental groups (n = 10): Control group treated with vehicle and groups EESe 500, EESe 1000 and EESe 2000 treated with doses 500, 1000 and 2000 mg /kg, respectively. In all studies, treatment occurred by gavage throughout the gestational period until the 18th day. Afterwards, parameters related to reproductive performance, embryofetal development and DNA integrity were evaluated. The results indicated that EEAl did not present adverse effects since it did not change the reproductive performance or even the embryofetal development in a significant way in the treated groups, in addition to not being genotoxic; EESl did not alter reproductive performance parameters and is not genotoxic. However, it altered embryofetal development by reducing placental weight, reducing fetal weight, increasing the frequency of small-for-gestational-age fetuses, and increasing the frequency of external, visceral, and skeletal malformations. With regard to the EESe, statistically significant changes were found in the biometric parameters of organs such as the heart and lungs. An increase in the number and rate of resorptions was observed, in addition to a slight increase in external, visceral and bone malformations, but it did not show genotoxicity. Given the above, it is considered that EEAl is not maternal toxic, does not alter reproductive performance, does not have teratogenic potential or genotoxicity. EESl is not maternal toxic, does not alter reproductive performance, is not genotoxic, but alters embryo-fetal development, and due to its teratogenic potential, its use in the gestational period is not recommended. Regarding EESe, it was observed that it was maternal toxic at a dose of 2,000mg/Kg, as it led all individuals to death, and at lower doses, it did not show maternal toxicity or genotoxicity. EESe is embryofetotoxic as it increased the number and rate of reabsorption and has low teratogenic potential. Therefore, its consumption during pregnancy is contraindicated. Key words: teratogenesis, mutagenesis, genotoxicity, medicinal plants.